Anthony McCall: Light, Space, and Time - Glen R. Brown (Oz, 2008)
In the silence of a darkened interior, a mesmerizing cone of light projects from ceiling to floor in luminous semblance of solidarity. Almost imperceptibly, this geometric form—existing solely as radiant energy yet imposing itself initially upon the mind as a concret object—begins to assert its immateriality, fading gradually over a 16-minute period into absolute darkness.